Assessing the Impact of the COVID-19 Pandemic on Tourism Workers’ Health and Well-being in Jordan - Mukhles M. Al-Ababneh; Firas J. Al-Shakhsheer; Ma'moun A. Habiballah; Mohammad B. Al-Badarneh (Tourism & Management Studies)
The current study assesses the impacts of the coronavirus (COVID-19) pandemic on tourism workers in Jordan between mid-March 2020 and June 2021 by investigating corona threats, financial impacts, resources impacts, social isolation, depression and personal control experienced by tourism workers during the COVID-19 pandemic, and how the threats of corona, financial impacts, resources impacts, social isolation, depression and personal control affect workers’ personal health and well-being. A quantitative survey method was applied by using a questionnaire. Data were collected from a sample of 400 workers from the tourism sector in Jordan. The study’s hypotheses were tested by using the Smart Partial Least Square (PLS) 3.3.3 Statistical Software. The findings of the study revealed that tourism workers are financially strained, socially isolated, psychologically depressed, uncontrolled their self, and have limited resources as a result of their dread of the pandemic and its negative impacts. It was also found that a significant negative direct effect of perceived coronavirus threats, financial impacts, resources impacts, and social isolation on workers’ depression and personal control, which in turn had a significant influence on workers’ personal health and well-being. In addition, this study proposed a model of the influence of coronavirus threats and its impacts on workers’ personal health and well-being, whereby workers’ depression and personal control fully mediate these relationships. The current study offers additional insights on the COVID-19 pandemic impacts on tourism workers’ personal health and well-being.